Challenges in Understanding the Risks to Natural and Semi-Natural Vegetation from Ozone Exposure - J. Neil Cape; Serain Bassin; Jürg Fuhrer; Giacomo Gerosa; Rocio Alonso; Benjamin Gimeno; Ludger Grünhage; Teis N. Mikkelsen; Gina Mills (Italian Journal of Agronomy)
The effects of tropospheric ozone on crops and forests have been studied intensively, but effects on natural and semi- natural plant communities are poorly understood. This lack of understanding arises partly from a lack of experimental studies of whole mature communities, and the effects of ozone on competition and interactions with climate, nutrition etc., and partly from a lack of knowledge of the factors which predispose individual plant species to ozone damage. A recent review of the effects of ozone on grasslands (Bassin et al., 2007a) has drawn attention to the problems involved; this paper seeks to identify the practical issues that must be addressed in improving our knowledge and thereby identifying the risks associated with ozone exposure. This is a necessary first step before mitigation strategies can be developed.